Effectiveness of autologous haematopoietic stem cell transplantation versus natalizumab in progressive multiple sclerosis - Kalincik, Tomas; Sharmin, Sifat; Roos, Izanne; Massey, Jennifer; Sutton, Ian; Withers, Barbara; Freedman, Mark S; Atkins, Harold; Krasulova, Eva; Kubala Havrdova, Eva; Trneny, Marek; Kozak, Tomas; et al. (Journal of neurology, neurosurgery, and psychiatry, 2024)
BACKGROUND: Natalizumab was not shown to modify disability in progressive multiple sclerosis (MS). This matched observational study compared the effectiveness of autologous haematopoietic stem cell transplantation (AHSCT) with natalizumab in progressive MS. METHODS: Patients with primary/secondary progressive MS from seven AHSCT MS centres and the MSBase registry, treated with AHSCT or natalizumab, were matched on a propensity score derived from sex, age, Expanded Disability Status Scale (EDSS), number of relapses 12/24 months before baseline, time from MS onset, the most effective prior therapy and country. The pairwise-censored groups were compared on hazards of 6-month confirmed EDSS worsening and improvement, relapses and annualised relapse rates (ARRs), using Andersen-Gill proportional hazards models and conditional negative binomial model. RESULTS: 39 patients treated with AHSCT (37 with secondary progressive MS, mean age 37 years, EDSS 5.7, 28% with recent disability progression, ARR 0.54 during the preceding year) were matched with 65 patients treated with natalizumab. The study found no evidence for difference in hazards of confirmed EDSS worsening (HR 1.49, 95% CI 0.70 to 3.14) and improvement (HR 1.50, 95% CI 0.22 to 10.29) between AHSCT and natalizumab over up to 4 years. The relapse activity was also similar while treated with AHSCT and natalizumab (ARR: mean±SD 0.08±0.28 vs 0.08±0.25; HR 1.05, 95% CI 0.39 to 2.82). In the AHSCT group, 3 patients experienced febrile neutropenia during mobilisation, 9 patients experienced serum sickness, 6 patients required intensive care unit admission and 36 patients experienced complications after discharge. No treatment-related deaths were reported. CONCLUSION: This study does not support the use of AHSCT to control disability in progressive MS with advanced disability and low relapse activity.
Keywords: Disease Progression; lidé; Middle Aged; výsledek terapie; Adult; natalizumab; Natalizumab; Female; Transplantation, Autologous; posuzování pracovní neschopnosti; chronicko-progresivní roztroušená skleróza; progrese nemoci; Humans; Disability Evaluation; Hematopoietic Stem Cell Transplantation; autologní transplantace; lidé středního věku; mužské pohlaví; transplantace hematopoetických kmenových buněk; ženské pohlaví; Multiple Sclerosis, Chronic Progressive; Immunologic Factors; imunologické faktory; Treatment Outcome; Male; dospělí